Association of germline variants in the ZFX gene with primary hyperparathyroidism - Ainhoa Camille Aranaga-Decori; Pedro González; Sara Gómez-Conde; Leire Madariaga; Nuria Valdes; Luis Castaño; Alejandro García-Castaño (PLoS ONE, 2025)
Somatic variants in the ZFX gene have been found in human sporadic parathyroid adenomas. This gene encodes a transcriptional factor recently described as a transcriptional activator in multiple types of human tumors. We present the clinical and molecular characterization of three patients diagnosed with primary hyperparathyroidism (PHPT) who have germline variants in the ZFX gene. The first patient had a pathogenic missense variant (c.2321A > G; p.(Tyr774Cys)) in the heterozygous state. This patient exhibited PHPT along with ear, nose and forehead abnormalities. Additionally, she presented other characteristics seen in patients with pathogenic variants in the ZFX gene, such as hearing loss and multiple cutaneous nevi. The second and third patients had a missense variant of uncertain significance (c.1606C > T; p.(Arg536Cys)) and an in-frame insertion (c.452_460dup; p.(Gly151_Val153dup)) of uncertain significance, respectively, both in the heterozygous state. These patients had no hearing loss, cutaneous melanocytic nevi, or bone or facial deformities. ZFX may be one of the genes to be analyzed in women affected by PHPT with suspected genetic inheritance, especially if they have other features such as facial deformities, hearing loss, and cutaneous melanocytic nevi.